THE WAY OF PROPHET MUHAMMAD (صلى الله عليه و سلم) - Sadiq, Muhammad, author 653674 (Riyadh : Darussalam, 1996)
This book presents the right way for the Muslims to live up to the standards set by the Qur'an and Sunnah so that the success in this life and the life hereafter can be realised. Each aspect related has been supported by the Verses and Ahadith to give the true perspective of the right way so that it can be adopted accordingly.